Aktuelle Forschung in der Gartenbauökonomie: Digitalisierung und Automatisierung - welche Chancen und Herausforderungen ergeben sich für den Gartenbau? Tagungsband zum 3. Symposium für Ökonomie im Gartenbau am 15. November 2019 in Freising/Weihenstephan - Walter Dirksmeyer; Klaus Menrad (Johann Heinrich von Thünen-Institut, 2021)
– The third Symposium of Economics in Horticulture was organized by the Department of Horticulture and Food Technology at Weihenstephan-Triesdorf University of Applied Sciences and the Thünen-Institute of Farm Economics. It took place at the 15th of November 2019 at Weihenstephan-Triesdorf University of Applied Sciences in Freising / Weihenstephan. During the first part of the symposium, the theme "Digitization and automation - what opportunities and challenges arise for horticulture?" was addressed in invited keynotes from research and horticultural practice. Also, in this context, the Federal Ministry of Food and Agriculture (BMEL) and the Federal Agency for Agriculture and Food (BLE) reported on the current status of innovation funding for Horticulture 4.0. The respective projects will be running until 2022 or 2023. The second major focus of the symposium were ten presentations on recent and ongoing research in horticultural economics. These contributions addressed the research fields "Marketing and sale of horticultural products" and "Farm economics in horticulture". In both thematic blocks, sustainability aspects played a major role. In the first block, for example, the demand for fair trade roses was analyzed or the question of whether insect protection in horticulture has a positive effect on sales was addressed, while in the second block case studies on food waste in the fruit and vegetable sectors were presented and projects on emission free soft fruit production and the economic effects of reducing the use of peat in horticulture were presented. In addition, the inter-company comparison in horticulture 4.0 was introduced and a paper on the reputation of German horticulture was discussed. In this Thünen Report 89 the symposium papers are presented.
urn:nbn:de:gbv:253-202110-dn064048-4
Keywords: Q11; Q12; Q13; Q15; Q16; Q56; 630; Horticultural economics; digitization; automation; horticulture 4.0; sustainability